TBLT Perspectives on Teaching from an EFL Textbook at a Vietnam University - Dao, Hao; Newton, Jonathan (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2021)
This study investigated the relationship between the affordances for task-based teaching in a textbook and teachers’ awareness of and uptake of these affordances. Specifically, it compared and evaluated the communicativeness and task-likeness of activities in the textbook, New Cutting Edge, Elementary (Cunningham & Moore, 2005) and then contrasted these findings with classroom observation data on the way the activities were implemented by three Vietnamese English as a Foreign Language (EFL) teachers at a Vietnamese university. Interviews with the teachers provided further data on their implementation decisions. The analysis and evaluation of the textbook activities and how they were implemented adopted two coding frameworks, one for evaluating communicativeness (Littlewood, 2004) and the other for evaluating task-likeness (Ellis, 2018). The analysis of communicativeness revealed that while the textbook has a high proportion of activities with low communicative value, the task analysis showed that many of these activities are, in fact, either tasks or task-like. However, form-focused activities typically precede the tasks, which compromises the alignment of the textbook with TBLT. Data from classroom observations of three 90-minute lessons taught by each teacher showed that the teachers consistently reduced the communicativeness and task-likeness of the textbook activities, and replaced them with teacher-centered, explicit grammar explanation and drill practice. Stimulated recall interviews and follow-up semi-structured interviews revealed the teachers’ rationales for their practice, including their concern about the unsuitability of tasks for low proficiency students, exam pressure and time constraints, and their lack of awareness of the nature of language learning tasks.